Hysteresis Current Control of Switched Reluctance Motor in Aircraft Applications - Maged N. F. Nashed; Samia M. Mahmoud; Mohsen Z. El-Sherif; Emad S. Abdel-Aliem (Institute of Advanced Engineering and Science, 2014)
The switched reluctance motor (SRM) drives have been widely used in aircraft applications due to the motor advantages like high speed operation, simple construction, no windings on rotor. But high torque ripples and acoustic noise are main disadvantages. The current hysteresis chopping control is one of the important control methods for SRM drives. These disadvantages can be limited using the hysteresis or chopping current control. This control strategy makes the torque of SRM maintained within a set of hysteresis bands by applying suitable source voltage. This paper introduces two hysteresis control modes; hard chopping and soft chopping mode. The SRM drive system is modeled in Simulink model using MATLAB/SIMULINK software package.DOI: http://dx.doi.org/10.11591/ijpeds.v4i3.6210